USING NETWORK COMMUNITY IN TEACHING OBJECT-ORIENTED PROGRAMMING OF BACHELORS OF PEDAGOGICAL EDUCATION - Diana V. Moglan (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article is devoted to the ways of teaching object-oriented programming of bachelors of pedagogical education in network community. The author considers educational possibilities of network community, pedagogical features of teaching of object-oriented programming using educational network communities. The article presents a model of the educational network community built using Web 2.0 services - blogs. The author defined technological and didactic properties and didactic function of the blog. The author presented the content of discipline “Object-Oriented Programming” and described the work of bachelors for the study sections of the discipline in a network community.